Analysis of water quality on growth performance bamboo lobster (Panulirus versicolor) in Tanjung Limau, Bontang City, East Kalimantan - Andriawan, Soni; Fahreza, Mohammad Adam; David, Hermawan; Handajani, Hany (Acta Aquatica: Aquatic Sciences Journal, 2023)
Lobster is one of the commodities that have high economic value in the world market. Thus, the export opportunities for lobster commodities are still promising. One area that can produce lobster in Indonesia is Bontang, East Kalimantan. The area which is the sea waters is very potential for lobster rearing cultivation. This study was conducted with the aim of analyzing good water quality in lobster rearing cultivation in Bontang, East Kalimantan. The study used 3 floating net cages by taking water samples 4 times and 5 lobsters each sampling. Water quality samples include physics (color, smell and taste, temperature, brightness), chemistry (pH, DO, nitrite, salinity), biology (coliform), heavy metals (hg, pb, cu). Lobster samples were measured by weight. The results showed that Fsignificant > 0.05 so that the water quality parameters had no effect on growth. The cause of the ineffectiveness of water quality parameters is due to the contamination of waters in Bontang, East Kalimantan.Keywords: Bamboo Lobster; Contamination; Floating Net Cage; Heavy Metal.